2018
DOI: 10.1002/chem.201802201
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy of “Self‐Isolated Enhanced Emission” to Achieve Highly Emissive Dual‐State Emission for Organic Luminescent Materials

Abstract: Currently, the commonly developed organic luminescent materials (OLMs) usually exhibit poor luminescent performance in aggregated solid states compared with their well-dissolved solution states, making it a tough goal to achieve the highly emissive dual-state emission. To overcome this limitation, a "self-isolated enhanced emission" (SIEE) strategy through flexible alkyl chains to suppress the emission-quenched π-π stacking in solids is proposed here and, based on this guideline, remarkable emission efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…One major strategy to design DSEgens is to add conjugation‐induced rigidity in twisted molecules, for which conjugation‐induced rigidity facilitates the emission in solution by suppressing intramolecular rotation and vibration, and twisted structures are used to avoid fluorescence quenching in the solid state caused by π–π stacking . Dual‐state emission can also be attained by incorporating bulk substituents into molecular structures to prohibit π–π stacking in the solid state . A zero‐twist donor–acceptor molecule was also found as a dual‐state emitter, and a recent study showed that D –π–A structures can be used to achieve DSE properties .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One major strategy to design DSEgens is to add conjugation‐induced rigidity in twisted molecules, for which conjugation‐induced rigidity facilitates the emission in solution by suppressing intramolecular rotation and vibration, and twisted structures are used to avoid fluorescence quenching in the solid state caused by π–π stacking . Dual‐state emission can also be attained by incorporating bulk substituents into molecular structures to prohibit π–π stacking in the solid state . A zero‐twist donor–acceptor molecule was also found as a dual‐state emitter, and a recent study showed that D –π–A structures can be used to achieve DSE properties .…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9] Dual-state emissionc an also be attained by incorporating bulk substituents into molecular structurest op rohibit p-p stacking in the solid state. [10] A zero-twist donor-acceptor molecule was also found as ad ualstate emitter, [11] and ar ecent study showed that D-p-A structures can be used to achieve DSE properties. [12] However,t here is no valid design strategy for designing DSEgens with solvatochromism because of the lack of an investigation into the relationship between structure and DSE property.…”
mentioning
confidence: 99%
“…[27][28][29][30][31] By using these highly emissive AIEgens, dual-state emission can be easily achieved and they have potential real-world applications, [32][33][34] such as in PA detection and LFP visualization. Recently,f lexible alkyl chains were introduced into conventionalf luorescent molecules to prevent close packing of their core structures as well as strong p-p intermolecular stacking interactions, [35][36][37] thereby openingr adiative channels to afford highlye missive features in aggregates.T herefore, based on these considera-tions, to achieve ah ighly efficient dual-state emission platform for PA detection and LFP visualization,i nt his work, flexible alkyl chains were facilelya ttached to the commercial organic dye 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)t o afford the tetraalkyl 3,4,9,10-perylenetetracarboxylate target compounds PTCA-C4, PTCA-C6, and PTCA-C12 (fort he structures, see Figure 1). As we anticipated, impressive fluorescence characteristics with photoluminescence quantum yields (PLQYs) of up to 95.0, 96.9, and 93.2 %w ereo btained for PTCA-C4, PTCA-C6, and PTCA-C12 in THF solution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the key intermediate compounds 2-(4-octylphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (2a), 2-(4-octyloxyphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (2b) and 2-bromoanthracene (3) were prepared according to previously reported procedures. 38,[40][41][42] Subsequently, the target materials AntPh-C8, AntPh-OC8 and AntPh were synthesized by using 2-bromoanthracene (3) and the corresponding pinathol borate esters (2a, 2b and 2c) via a Suzuki-Miyaura coupling reaction. High-purity materials were obtained by gradient vacuum sublimation two to three times.…”
Section: Synthesismentioning
confidence: 99%